Ethnic and Racial Stereotypes: A Critical Appraisal of Identity Politics in Nepal - Paudel, Ram Chandra (Crossing the Border: International Journal of Interdisciplinary Studies, 2014)
As per the scope of this paper, it attempts, in its first part, to offer an operational definition of the term "stereotype." Then it scrutinizes three visual images to demonstrate how racial /ethnic stereotypes are constructed. The first image is extracted from Jo Sharp's Geographies of Postcolonialism. The second image comes from Mike Chappel's The Gurkhas and the third carton sketch is taken from The Kathmandu Post. In its final part, the paper explains how some ethnocentric elites in Nepal, motivated and funded by western agencies, are attempting to homogenize /stabilize the complex social racial and ethnic texture. The paper concludes that such stereotypical and monolithic representations can provoke racial and ethnic issues resulting in disintegration, xenophobia and conflict in Nepali society. DOI: http://dx.doi.org/10.3126/ctbijis.v1i1.10471 Crossing the Border: International Journal of Interdisciplinary Studies Vol.1(1) 2013; 79-84